1981
DOI: 10.1083/jcb.91.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Kinetochore structure, duplication, and distribution in mammalian cells: analysis by human autoantibodies from scleroderma patients.

Abstract: The specificity of the staining of CREST scleroderma patient serum was investigated by immunofluorescence and immunoelectron microscopy. The serum was found to stain the centromere region of mitotic chromosomes in many mammalian cell types by immunofluorescence. It also localized discrete spots in interphase nuclei which we have termed "presumptive kinetochores ." The number of presumptive kinetochores per cell corresponds to the chromosome number in the cell lines observed . Use of the immunoperoxidase techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
117
1
3

Year Published

1982
1982
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(126 citation statements)
references
References 19 publications
4
117
1
3
Order By: Relevance
“…Meiosis in Brca2 À/À rats proceeds normally through leptotene and early zygotene (Figure 3a) with 40 centromeres clearly identified by CREST antisera (Brenner et al, 1981). The correct number of centromeres and chromosome cores indicates that sister chromatid cohesion is not affected in the absence of Brca2.…”
Section: Aspermatogenesismentioning
confidence: 99%
“…Meiosis in Brca2 À/À rats proceeds normally through leptotene and early zygotene (Figure 3a) with 40 centromeres clearly identified by CREST antisera (Brenner et al, 1981). The correct number of centromeres and chromosome cores indicates that sister chromatid cohesion is not affected in the absence of Brca2.…”
Section: Aspermatogenesismentioning
confidence: 99%
“…The mitotic apparatus is an appealing context for the use of such spatial domain techniques because it contains discrete structures that can be manipulated in order to address their respective roles in the production of pulling or pushing forces to move chromosomes during mitosis. Accordingly, laser microsurgery has been seminal to elucidate the mechanistic basis of the spindle-assembly checkpoint (2), the role of the centrosome in spindle assembly (3) and the role of kinetochores in chromosome movement (4)(5)(6). We believe that we can significantly broaden this scenario by combining powerful live cell imaging and state-of-the-art laser technology with molecular tools.…”
Section: Introductionmentioning
confidence: 99%
“…Additional information concerning the distribution of interphasic centromeres and the extent of their possible redistribution between late G 2 and metaphase is paramount when one tries to interprete such data in terms of an interphase chromosome arrangement. For example, it makes an important difference whether centromeres are clustered in a limited portion of the nucleus either at the nuclear edge (Rabl 1885) or elsewhere (Del Fosse and Church 1981) or distributed largely at random (Brenner et al 1981). Recent studies of the distribution of interphasic centromeres indicate considerable variation in cell types from different plant and mammalian species (Church and Moens 1976;Del Fosse and Church 1981;Moroi et al 1981;Brenner et al 1981).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it makes an important difference whether centromeres are clustered in a limited portion of the nucleus either at the nuclear edge (Rabl 1885) or elsewhere (Del Fosse and Church 1981) or distributed largely at random (Brenner et al 1981). Recent studies of the distribution of interphasic centromeres indicate considerable variation in cell types from different plant and mammalian species (Church and Moens 1976;Del Fosse and Church 1981;Moroi et al 1981;Brenner et al 1981). Thirdly, and probably most important, the technical procedures routinely used for obtaining well spread metaphases (often including colchicine treatment and hypotonic shock) alter the chromosome arrangement of the intact metaphase plate to an extent which has not been documented by most investigators, although it can be shown that the relationship between chromosome arrangements at interphase and metaphase is critically influenced by the experimental regimen followed (Schmid et al 1981).…”
Section: Discussionmentioning
confidence: 99%